Civic countermarks on the silver coinage of Asia Minor in the 2nd century BC - Meadows, A (Suna and İnan KIRAÇ Research Institute on Mediterranean Civilizations, 2018)
In general the countermarking of Attic weight coins is comparatively rare, and when it occurs, appears from the surviving evidence to be highly episodic. Assembly of the material suggests that there are five main phenomena. The focus of this paper will be the fifth episode, which belongs to the 2nd century BC, as we shall see. But for comparison and contrast it is worth summarizing the earlier episodes first.